Analyzing the Effect of the Construction Safety Audit Model Using the Business Process Model and Notation (BPMN) Method on Improving Communication and Collaboration Between Stakeholders. - Ghazali, Muhammad; Nugroho, Danang Budi; Latief, Yusuf (CSID Journal of Infrastructure Development, 2024)
The significant increase in infrastructure development is directly proportional to the rising accident rate in the construction sector, making it one of the highest-risk sectors for accidents. This phenomenon indicates that existing construction safety audits have not been effective in preventing accidents, largely because audits are generally conducted only at the construction stage. Audits at the design stage, however, have the potential to impact accident prevention significantly. Therefore, this research aims to develop a construction safety audit model using the Business Process Model and Notation (BPMN) and analyzes the impacts on stakeholder communication and collaboration. BPMN was chosen because it provides a clear and standardized visual representation of business processes, making it easier to identify potential safety issues and improve stakeholder understanding. Statistical methods were employed to examine the relationships, resulting in a linear equation model with a strong correlation. Furthermore, audit activities conducted through three layers of stakeholders can be efficiently modeled using BPMN, positively impacting stakeholder communication and collaboration. Applying the Three Lines of Defense (TLoD) theory and BPMN provides new insights for construction safety committees and companies to plan and conduct more comprehensive safety audits. The implication of this study includes a potential reduction in construction accidents and improved work safety through more effective communication and collaboration among stakeholders.